Interaction between C60 and gases under pressure - Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
A brief review is given of the interaction between fullerite C60 and various gases under elevated pressure. Subjects discussed include the formation of ordered interstitial gas-fullerene compounds, reactions between intercalated gases and fullerene molecules to form new endohedral and exohedral compounds, and changes in the structure and properties of C60 because of intercalated gas atoms or molecules.